Conservative Management and Planned Surgery for Periviable Advanced Extrauterine Abdominal Pregnancy with Favorable Outcome: Report of Two Cases - Hassan M. Harirah; J. Michael Smith; C. Luke Dixon; Gary D. V. Hankins (Thieme Medical Publishers, Inc., 2016)
Abstract Advanced abdominal pregnancy is an extremely rare condition that poses diagnostic and management challenges. A high index of suspicion and careful assessment of the patient's symptoms, supplemented with obstetric ultrasound, and magnetic resonance imaging, are crucial for timely diagnosis and management to prevent life-threatening complications. The presence of periviable fetuses in advanced abdominal pregnancies increases the challenge to achieve a balance between maternal and fetal benefits and risks. Early diagnosis and management decisions via a multidisciplinary approach and planned delivery are of paramount importance to minimize complications and achieve favorable maternal and fetal outcomes. Even in the setting of oligohydramnios and suspected preterm premature rupture of membranes, in-patient conservative management and an individualized planned surgical approach that includes removing or leaving the placenta in place are appropriate for managing the periviable abdominal pregnancy.